Pedagogical Seminary. (Worcester, Mass. J.H. Orpha, 1891)
Vols. 5-15 include "Bibliography of child study," by Louis N. Wilson.
"An international record of educational literature, institutions and progress."
Keywords: Education -- Periodicals; Psychology -- Periodicals; Child psychology -- Periodicals